MANIFESTO OF PB - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2019)
What is happening to architecture?For several decades, starting from the publication of Hundertwasser’s Manifesto, we have heard: “Architecture is seriously ill. Architecture is going to die”. Many prominent voices are already singing for the repose of its soul.In the past, architecture experienced the highest rises. Classical antiquity, mature Middle Ages, Modern and Constructivism – during those periods architecture acquired the best things produced by science, art and craft. It took from science a precise problem statement, logic and succession of methods, as well as mathematical precision of thinking. It took from art the courage in dealing with motions of the soul, the constant searching for new forms and a keen interest towards achievements of previous generations. It took from craft the skills of dealing with the material, respect towards the practical experience and commitment to economic efficiency. It is no wonder that in its flourishing periods architecture was a role model in the broadest sectors of culture, from politics to fashion.It seems that, within recent decades, architecture set out to take only drawbacks and vices from the same fields. It borrows from science a tendency to the scholastic and pointless playing with terms. From art – egoistic subjectivism and endless intrigues. From craft – monotony and boredom of standardized flow production. Seriously ill architecture chooses not even the greater evils, but all the evils from this variety.Anyway, throughout the history of mankind architecture has not been more timely than today. The mass movement of people to cities poses great challenges. Rural habitat is full of life. Nature itself fills it with living characters, rhythms and Life and Death cycles. The urban environment is created by humans from nonliving materials. This man-made environment offers no chance for a harmonizing impact of nature – the urban ecosystem is too simple, monopolar and dependent upon humans. In regards to emotions, today’s city looks as unsanitary and pathogenic as a medieval city used to look in regards to everyday hygiene. Contemporary citizens pour out their anger, disgust and despair like it used to be with pigwash up to the 19th century. Today’s pandemic of depression is similar to plague and cholera that devastated Europe in the past centuries.Only healthy and proper architecture open for the best can relieve cities from their disaster and turn the global urbanization into a more sensible and healthy channel. To do this, architecture has to thoroughly reconsider its methodological tools.Fifteen years ago PROJECT BAIKAL journal was founded by architects of the 1960s and their apprentices. Since then, professional scientists, artists and designers have been contributing to the journal. Throughout its 60 issues, the journal has been speaking about the possibility to combine the best and the most efficient features of science, art and craft. With that, the journal found like-minded fellows in different cities of Russia and other countries.We have reasons to be optimistic.
Keywords: architecture; science; art; craft; urban environment